Production mechanisms and their implications for Iraqi theater techniques (Al-Academy, 2022)
Theatrical production mechanisms were determined according to the extents of the theatrical performance, the directing plan, and the ideas that the theatrical performance seeks to convey to the audience. Accordingly, theatrical production mechanisms differ between one theatrical performance and another according to the requirements of each of them and the surrounding circumstances that accompany the production of theatrical performance, and in order to search for production mechanisms and their repercussions on the show. Theatrical The current research was divided into four chapters, namely (Chapter One - Methodology), which identified the research problem in the following question: What are the production mechanisms and their implications for the techniques of Iraqi theatrical performance? The aim of the research came according to the question of the problem, as well as the terminology was defined, while the second chapter (the theoretical framework) came in three sections (1- The concept of theatrical production mechanisms, 2- Management and planning in theatrical performance, 3- The production mechanism and techniques of theatrical presentation). As for the third chapter (research procedures) choosing a play (Silphon) and it was analyzed within the descriptive analytical approach, while the fourth chapter (results and conclusions) concluded the research with a list of sources.